Scientific production on knowledge management, information management and document management between 2010 and 2021 (Ágora de Heterodoxias, 2022)
The analysis of scientific production for research is established under the “pillar of information” in which knowledge, information and document management converge. The three terms also converge with the disciplines of archival and documentation, although in recent times they have been dispersed. This bibliometric study was carried out using data from the Scopus platform for the period 2010-2021, which show that in scientific publications on knowledge management, articles published in Portuguese and English have a greater role; while in document management there is the smallest record of scientific publications. The general productivity of the pillar (information management, document management and knowledge management) is the publication of conferences, products of articles to be presented at academic events, which reveals a new trend to be reviewed.
Keywords: Information management; Knowledge management; Document management; Scientific production; Bibliometric indicators